HUBUNGAN ANTARA ASUPAN ENERGI DAN PROTEIN DENGAN STATUS GIZI IBU HAMIL DI WILAYAH KERJA PUSKESMAS BERGAS KABUPATEN SEMARANG - Anisatul Mahmudah; Basuki Sigit (JURNAL RISET GIZI, 2015)
Background : Pregnant women are one of the nutrition vulnerable groups. The impact of the lack of nutrition caused due to poor nutritional status in pregnant women is not only in mothers but in babies born and later growth and development of babies. The Prevalence of Chronic Energy Deficiency (SEZ) in 2013 was 22.2%. While the prevalence of Chronic Energy Deficiency (SEZ) in the work area of Bergas Puskesmas in Semarang Regency is 13.3% in 2014. Objective: . This study aimed to determine the relationship between energy and protein intake with nutritional status of pregnant women in the work area of Bergas Health Center, Semarang Regency. Methods: This study was a descriptive analytic study with a cross sectional design. A sample of 45 people with trimester II and III pregnancies. To find out the relationship between variables used the fisher exact test. Results: The results of the study showed that 26.67% of pregnant women suffered from SEZ, 33.3% of pregnant women had good energy intake, while 48.89% of pregnant women had good protein intake. While statistical tests show, there is a relationship between energy intake and nutritional status of pregnant women (p = 0.038), there is a relationship between protein intake and nutritional status of pregnant women (p = 0.17)